PRELIMINARY STUDY ON THE CONTENTS OF THE DIGESTIVE TRACT OF THE FISH Sicyopus zosterophorus (Bleeker, 1856) FROM THE BOHI RIVER, BANGGAI DISTRICT, CENTRAL SULAWESI - Gani, Abdul; Nurjirana, Nurjirana; Bakri, Achmad Afif; Adriany, Devita Tetra; Khartiono, Lady Diana; Herjayanto, Muh.; Burhanuddin, Andi Iqbal; Serdiati, Novalina; Ndobe, Samliok (Jurnal Ilmu Kelautan SPERMONDE, 2024)
ABSTRACT Sicyopus zosterophorus (Gobiidae) has a habitat in clear and fast-flowing rivers. This fish species is found in several rivers in Banggai Regency, Central Sulawesi, one of which is the Bohi River. Studies on the type of food S. zosterophorus in the Bohi River have never been carried out. Therefore, it is necessary to conduct research that aims to determine the type of food S. zosterophorus in nature as important information for life history and feeding in controlled habitats. This research was carried out from December 2019 to January 2020. The fishing was done using a scoop net by snorkeling to get fish at the bottom of the river. The fish obtained were then preserved using 5% formalin and then taken to the laboratory for identification of digestive tract contents. Data on the composition and percentage of types of food in the digestive tract were processed using Microsoft Excel 2010 and analyzed descriptively. The results showed that the contents of the digestive tract of S. zosterophorus were dominated by insects (74%), crustaceans (7%), plants (5%), and phytoplankton (3%). The contents of the digestive tract were not identified as much as 11%. Based on this, S. zosterophorus in the Bohi River is categorized as stenophagic and is a carnivorous fish, especially insectivorous and phytobenthic eaters. This research can be used as a basis for providing natural food for S. zosterophorus in aquaculture. Keywords: Goby fish, insectivorous, phytobenthic, stenophagic